1997
DOI: 10.1074/jbc.272.38.23938
|View full text |Cite
|
Sign up to set email alerts
|

Avian Retrovirus U3 and U5 DNA Inverted Repeats

Abstract: The U3 and U5 termini of linear retrovirus DNA contain imperfect inverted repeats that are necessary for the concerted insertion of the termini into the host chromosome by viral integrase. Avian myeloblastosis virus integrase can efficiently insert the termini of retroviruslike DNA donor substrates (480 base pairs) by a concerted mechanism (full-site reaction) into circular target DNA in vitro. The specific activities of virion-derived avian myeloblastosis virus integrase and bacterial recombinant Rous sarcoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 30 publications
(38 reference statements)
2
17
1
Order By: Relevance
“…However, a qualitative visual inspection of the gels revealed the rapid appearance of U3 joining products within 15 s and a delayed onset of U5 joining products for 120 s even though the formation of both U3 and U5 processing products occurred within the first 5-10 s of the reaction. These results extend previous reports that integrase favors U3 over U5 (14,25) and illustrate the importance of having both U3 and U5 sequences present for the correct assembly of an integrase-LTR productive complex. This suggests that after processing, the joining activity of integrase is ordered such that the U3 end of the viral LTR is inserted prior to the U5 LTR.…”
Section: 44supporting
confidence: 79%
See 3 more Smart Citations
“…However, a qualitative visual inspection of the gels revealed the rapid appearance of U3 joining products within 15 s and a delayed onset of U5 joining products for 120 s even though the formation of both U3 and U5 processing products occurred within the first 5-10 s of the reaction. These results extend previous reports that integrase favors U3 over U5 (14,25) and illustrate the importance of having both U3 and U5 sequences present for the correct assembly of an integrase-LTR productive complex. This suggests that after processing, the joining activity of integrase is ordered such that the U3 end of the viral LTR is inserted prior to the U5 LTR.…”
Section: 44supporting
confidence: 79%
“…In the course of retroviral replication, the RNA genome is reverse-transcribed into a duplex DNA copy, and as a result of the strand-transfer mechanism of reverse transcriptase, the U5 and U3 sequences become the termini of the DNA genome (11). Purified integrase along with Mn 2ϩ or Mg 2ϩ as a cofactor is sufficient to catalyze both processing and joining reactions in in vitro assays using synthetic oligodeoxynucleotide substrates with DNA sequences derived from the U3 and/or U5 viral LTR ends (12)(13)(14).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The design of the 12-15 deletion mutant allowed the 12th position to remain wt with changes occurring at the 13th position and beyond. Previous results suggested that the nonsymmetrical nucleotides between avian U3 and U5 att sites at positions 8 and 12 did not appear to significantly influence either full-site or half-site strand transfer activities of IN (21). Each att DNA substrate was assembled with IN at several concentrations and the samples were subjected to DNase I probing and strand transfer.…”
Section: Dnase I Cleaves At Sensitive Att Site Nine Nucleotides From mentioning
confidence: 99%